Teaching and the Value of Inquiry - O'Leary, Paul (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2007)
This paper considers a self-acknowledged indoctrinator’s defense of his teaching. This defense relies on the correspondence conception of truth which allows a logical gap between the conduct of an inquiry and the truth of our beliefs. In criticism, I will seek to characterize the truth of our beliefs in terms of a link with genuine inquiry. Finally, I consider the value of having true beliefs and what constitutes the importance of acquiring the ability to inquire. On this view, good teaching, at a minimum, involves the exercise and the fostering of what I shall call epistemic prudence.